Competitiveness of Indonesian banking industry based on commercial bank business group: Panzar Rosse Model - Fajra Octrina; Rike Setiawati (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
The present research was aimed to investigating the competitiveness in Indonesian banking sector during the period of 2005 to 2016, to set the limit of the scope of the study a total sample is 84 banks. This research was conducted by grouping banks based on ownership and based on BUKU (General Bank based on Business Activities). The study also aimed to analyze the banking competitiveness based on classification of banks and groups of capital ownership. The study was conducted by evaluating the value of H-statistic for the research model comprising of three input variables, namely funds, labors and capital. The results of the research show that the market of banking industry in Indonesia is classified as monopolistic competition. The limitation of this study is that this study only looks at the competition variable, and has not seen its relationship with other variables. In subsequent studies, it is expected to conduct research related to competition and relate it to other variables, such as market share or level of market concentration.